Pemberian Pendidikan Kesehatan tentang Kekerasan Seksual pada Anak di PAUD Muslifa Kota Bengkulu - Elsi Rahmadani; Marlin Sutrisna; Ida Rahmawati (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2022)
Background: Sexual violence and sexual deviations that afflict children in their own environment are caused by a lack of sex education for children. The purpose of this community service is to increase mother's knowledge about preventing sexual violence in children. The method of implementation is counseling about the prevention of sexual violence in children. This Community Service activity was carried out at PAUD Muslifa Bengkulu. Implementation time in May 2022. Participants of this community service activity are mothers who have children aged 3-6 years at PAUD Muslifa Bengkulu with a total of 30 people. The activity is carried out in stages (1) providing an explanation of the prevention of sexual violence against children and the purpose of the activity; (2) provide knowledge about the prevention of sexual violence in children. The results of the activity showed that there was an increase in mother's knowledge about preventing sexual violence in children. After participating in this activity, mothers can apply knowledge about preventing sexual violence against children. Keywords: children, sexual violence, knowledge.